Antimicrobial Synergism Toward Pseudomonas aeruginosa by Gallium(III) and Inorganic Nitrite - Zemke, Anna C.; Madison, Cody J.; Kasturiarachi, Naomi; Pearce, Linda L.; Peterson, James (Frontiers in Microbiology, 2020)
The ubiquitous involvement of key iron-containing metalloenzymes in metabolism is reflected in the dependence of virtually all bacteria on iron for growth and, thereby, potentially provides multiple biomolecular targets for antimicrobial killing. We hypothesized that nitrosative stress, which induces damage to iron metalloproteins, would sensitize bacteria to the ferric iron mimic gallium(III) (Ga3+), potentially providing a novel therapeutic combination. Using both laboratory and clinical isolates of Pseudomonas aeruginosa, we herein demonstrate that Ga3+ and sodium nitrite synergistically inhibit bacterial growth under both aerobic and anaerobic conditions. Nitric oxide also potentiated the antimicrobial effect of Ga3+. Because many chronic pulmonary infections are found as biofilms and biofilms have very high antibiotic tolerance, we then tested the combination against biofilms grown on plastic surfaces, as well as the apical surface of airway epithelial cells. Ga3+ and sodium nitrite had synergistic antimicrobial activity against both biofilms grown on plastic and on airway epithelial cell. Both Ga3+ and various NO donors are (independently) in clinical development as potential antimicrobials; however, we now propose the combination to have some particular advantages, while anticipating it should ultimately prove similarly safe for translation to treatment of human disease.